Di-n-butyl phthalate exposure negatively influences structural and functional neuroplasticity via Rho-GTPase signaling pathways. (July 2017) - Ding, Yuemin; Lu, Lingchao; Xuan, Chengkai; Han, Jiajv; Ye, Shumin; Cao, Tingting; Chen, Weibo; Li, Aiqing; Zhang, Xiong
Abstract: Di- n -butyl phthalate (DBP) has been reported to cause disruptions in hippocampal plasticity, but its specific mechanism has not yet been ascertained. In this research, a mouse model of chronic DBP exposure was generated by intragastric administration of DBP (10, 50, or 250°mg/kg/d) for 5 weeks. Chronic exposure to high concentrations of DBP (250°mg/kg/d) induced a spatial learning deficit in the Morris water maze in male mice. By determining the activity of Rho-GTPase signaling pathways in the hippocampal tissues, we found that DBP exposure inhibited the activity of Rac1/PAK1/LIMK1 but activated RhoA/ROCK/LIMK2 signaling and eventually suppressed cofilin activity by phosphorylation. Consistent with this, the differential activation was also observed in the acute exposure model of neuronal cells generated by incubation with DBP (100°ng/ml, 1, 10, or 100°μg/ml) for 72 hours. Moreover, acute exposure to high concentrations of DBP (100°μg/ml) altered cell morphology by inhibiting neurite outgrowth. A ROCK inhibitor, but not inhibitors of Rac1 or PAK1, reversed the inhibition of DBP to the activity of cofilin and neurite outgrowth in cells. These findings provide the first evidence that DBP exposure results in impairment of neuroplasticity by differential regulation of Rho-GTPase signaling pathways. Graphical abstract: Highlights: Chronic oral exposure to DBP caused the impairment of spatial learning ability in adult male mice. DBP exposure inhibited the activity of Rac1/PAK1/LIMK1 and eventually inhibited cofilin activity. DBP incubation inhibited neurite outgrowth and migration in neuronal cells, which was revised by a ROCK inhibitor.